Obesity and bariatric surgery: an analysis between the bypass and sleeve techniques and their impacts on obese patient’s health (Research, Society and Development, 2023)
Objective: differentiate the most utilized techniques in bariatric surgeries, with the objective of disseminate concepts that involve this procedure has been growing considerably at the clinics and Brazilians hospitals. Method: integrative literature review, with search of published studies at the last 10 years, realized at database: Scientific Electronic Library Online (Scielo), US National Library of Medicine (Pubmed) and Virtual Health Library (VHL) in October 2022. The searches were obtained by the crossing, at the database, of the following descriptors: Bariatric Surgery, Gastroplasty, Public Heath, Obesity, Bypass Gastric and Gastrectomy. For the organization of the results, the flowchart was used advocated by PRISMA. Results: 10 articles were selected to compose this revision, and by the comparison between them, the different impacts of the Gastric Bypass and Sleeve Gastrectomy techniques on the heath of patients was evidenced, with focus on metabolic changes, physics, post surgery and resolution of chronicle diseases. Conclusion: The bariatric techniques Gastric Bypass and Sleeve Gastrectomy, belonging to rol of public Brazilian heath system, provide positives and significant impacts at human health, with better life quality, with a little, but meaningful superiority of gastric bypass.